PEMBERIAN KOMBINASI PUPUK ORGANIK TERHADAP DUA VARIETAS SORGUM (Sorghum bicolor L.) - Puspita, Fifi; ', Sugiharto; ', Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This reseach aims to determine the effect of interaction of organic fertilizer combination on the growth of two varieties of sorghum. The research was conducted experimentally by using Split Plot Design (SPD) that stacked as RAK pattern consist of main plot varieties CTY-33 and Numbu. Subplot consist of chicken manure fertilizer, chicken manure combined with vermicompost fertilizer and goat manure fertilizer combined with vermicompost fertilizer with 3 replications. Parameters measured were the plant height, stem diameter, number of leaves, panicle length, days to flowering. The results of research shows the best varietys is Numbu varietys, interactions of giving some organic fertilizer on two varieties of sorghum significantly affected on sorghum plant height. Application of organic fertilizers can increase the growth of sorghum plane. Treatment of 2 tons/ha- chicken manure in combinacion with 600 kg/ha- vermicompost fertilizer gave the best response to plant height and stem diameter compared with others.   Keywords : Chicken manure fertilizer, goat manure fertilizer, sorghum, vermicompost